2015
DOI: 10.1371/journal.pone.0133021
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Flora Changes in Conjunctiva of Rats with Streptozotocin-Induced Type I Diabetes

Abstract: BackgroundThe microbiota of both humans and animals plays an important role in their health and the development of disease. Therefore, the bacterial flora of the conjunctiva may also be associated with some diseases. However, there are no reports on the alteration of bacterial flora in conjunctiva of diabetic rats in the literature. Therefore, we investigated the changes in bacterial flora in bulbar conjunctiva of rats with streptozotocin (STZ)-induced type I diabetes.MethodsA high dose of STZ (60 mg/kg, i.p.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In spite of the protective effect of GEN on T1D among females, increased Erysipelotrichaceae (28), and decreased Escherichia (27), Lachnoslira (25), Firmicutes (other genus) and Enterococcus (29) at the genus level suggested a pro-inflammatory status in our GEN-treated NOD females. At the order level, increased Erysipetotrichalae (28) and Clostridia (other order), and decreased Firmicutes (other order) also indicated an exacerbating effect of T1D.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In spite of the protective effect of GEN on T1D among females, increased Erysipelotrichaceae (28), and decreased Escherichia (27), Lachnoslira (25), Firmicutes (other genus) and Enterococcus (29) at the genus level suggested a pro-inflammatory status in our GEN-treated NOD females. At the order level, increased Erysipetotrichalae (28) and Clostridia (other order), and decreased Firmicutes (other order) also indicated an exacerbating effect of T1D.…”
Section: Discussionmentioning
confidence: 60%
“…3C) and six at the genus level (Fig. 3D) were significantly increased following GEN treatment, suggesting a pro-inflammatory effect (25, 27-29). In addition, we have found that two diets used in this study had a differential effect (indicated by α-diversity, β-diversity, and taxonomy) on gut microbiome in VH females, which is in agreement with previous literatures (30).…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, the few vertebrate ocular microbiomes that have been characterized (humans, lab rats and koalas) were found to be dominated by members of the Phyla Actinobacteria and Proteobacteria (Dong et al ., ; Alfano et al ., ; Yang et al . ; Kugadas and Gadjeva, ; Shin et al ., ). Although Firmicutes have been identified in these microbiomes as well, they are at much lower relative abundance in comparison to the house finch ocular microbiome (Dong et al ., ; Lee et al ., ; Zhou et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…There are also numerous examples of resident microbiomes responding to pathogens (e.g. reduced gut biodiversity in swine following viral diarrheal infection [Koh et al, 2015]; reduced microbial diversity in reef-building corals infected with white plague disease [Cardenas et al, 2012]) and the ocular microbiomes of Sprague-Dawley rats were found to change in response to a non-infectious disease, type I diabetes mellitus (Yang et al, 2015). Overall, revealing the extent to which the composition of the microbiota shifts during infection is critical to understanding the role of the microbiome in disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was induced with a single intraperitoneal injection of STZ (60 mg/kg). [ 17 18 ] Three days later, blood glucose level was measured using glucometer (Accu-Chek Active, GC Model, Germany) and the rats with blood glucose levels above 250 mg/dl were considered as diabetic. The thirty adult female and thirty male diabetic rats were randomly assigned to 10 groups (female and male rats as groups 1–5 and groups 6–10, respectively, n = 6):…”
Section: Methodsmentioning
confidence: 99%